Ninth Five Year Plan 1997-2002 Draft Proposals Volume III (in Three Volumes) - Government of Haryana (Government of Haryana, 1997)
The draft proposals of the Ninth Five Year Plan (1997–2002) for Haryana under the Social and General Services Sector emphasize strengthening the education system, particularly through the expansion and universalization of primary education. The plan outlines financial allocations and programme targets for school and higher education, art and culture, and quality improvement initiatives. A central objective is achieving universal enrolment of children aged 6–10 years by 2001–2002 through increased enrolment, improved retention, and enhanced educational infrastructure. Based on projected population figures from the 1991 census, the state aims to enrol approximately 30.55 lakh children in primary classes. To meet this goal, the government proposes opening 1,000 new primary schools—primarily for girls in areas with low female literacy—and recruiting 5,000 additional JBT teachers, including staff for newly established schools. Infrastructure improvements include providing basic classroom facilities such as durri patti (floor mats), maintenance funds for equipment supplied under the Operation Blackboard Scheme, and expansion of educational facilities. The plan also introduces quality enhancement programmes such as calligraphy competitions, oral expression contests, debates, and cultural activities to improve students’ language and communication skills. Additionally, a publicity enrolment drive is proposed to increase awareness and encourage the enrolment and retention of children, particularly from Scheduled Castes and economically weaker sections. Incentive schemes and targeted support programmes are designed to promote educational participation among disadvantaged groups, while financial allocations are carefully structured within the constraints of available resources. Overall, the plan seeks to improve access, equity, and quality in the education system through infrastructural development, teacher recruitment, student support initiatives, and community awareness programmes.
Planning Department Government of Haryana. June, 1997
Planning Department Government of Haryana. June, 1997
Keywords: State Five Year Plan; Primary Education Universalization; School Education Expansion; Teacher Recruitment; Girls Education Promotion; Operation Blackboard Scheme; Educational Infrastructure Development; Student Enrolment Drive; Scheduled Castes Incentive Schemes; Quality Improvement Programmes; Educational Competitions; Publicity and Retention Campaign